2009
DOI: 10.1002/prep.200700288
|View full text |Cite
|
Sign up to set email alerts
|

Onset Temperatures in Hot Wire Ignition of AN‐Based Emulsions

Abstract: Hot wire ignition experiments were carried out recently at the Canadian Explosives Research Laboratory on a few emulsion formulations. The data indicate that there is a pressure-dependent onset temperature beyond which the wire temperature increases at an accelerated rate. In order to explain this observation and to detect this temperature more consistently, particularly at low pressures, the data are reanalysed by comparing the experimental wire temperature with that predicted from theory for the heating of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Such a configuration has, for example, been used in laboratory experiments on the burning of ammonium nitrate (AN), in the context of emulsion explosives [Turcotte et al .2008;Chan and Turcotte 2009]. The extensive literature on the dissociation of AN reveals a surprising variety of representations of the chemistry involved.…”
Section: Problem Description and Mathematical Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a configuration has, for example, been used in laboratory experiments on the burning of ammonium nitrate (AN), in the context of emulsion explosives [Turcotte et al .2008;Chan and Turcotte 2009]. The extensive literature on the dissociation of AN reveals a surprising variety of representations of the chemistry involved.…”
Section: Problem Description and Mathematical Modellingmentioning
confidence: 99%
“…Importantly, some are exothermic and some endothermic, and it has been common to assume a lumped representation of just two competing processes, one endothermic, for example [Sinditskii et al, 2005] In numerical simulations of the ignition of AN [Hughes et al 2011], self propagating fronts were not found when values of the kinetic parameters appropriate for 'pure' AN were used; this is in accord with the extensive literature on AN combustion. However, for values modified to take a crude account of the effect of additives [Chan and Turcotte 2009], such travelling combustion fronts were observed to develop for wide ranges of initial conditions and parameter values.…”
Section: Problem Description and Mathematical Modellingmentioning
confidence: 99%
“…S. K. Chan and R. Turcotte et al. established a testing system to study the thermal safety of emulsion matrix under different ambient pressure and proposed the minimum burning pressure concept and analyzed the key influencing factors. In addition, some scholars have studied the thermal safety of emulsion matrix in the screw pump.…”
Section: Introductionmentioning
confidence: 99%
“…Various MBP measurement methodologies for AWEs have been developed over the years [2 -4] and recent research has demonstrated that ignition source power and geometry play an important role in order to ensure reproducible localized thermal ignition in these explosives [5,6]. Consequently, in some of the MBP data collected previously, lack of propagation may have been confused with improper ignition.…”
Section: Introductionmentioning
confidence: 99%